1887 Mich. Pub. Acts 144 - (:unkn) unknown (My University, 1887)
No. 129, § 1: Prohibited the carrying of a concealed dirk, dagger, sword, pistol, air gun, stiletto, metallic knuckles, pocket-billy, sandbag, skull cracker, slungshot, razor or other offensive and dangerous weapon or instrument.
Keywords: CARRY - CONCEALED